2003
DOI: 10.2337/diacare.26.3.590
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Detemir Is Associated With More Predictable Glycemic Control and Reduced Risk of Hypoglycemia Than NPH Insulin in Patients With Type 1 Diabetes on a Basal-Bolus Regimen With Premeal Insulin Aspart

Abstract: OBJECTIVE -Insulin detemir is a soluble basal insulin analog with a unique mechanism of protracted action designed to reduce the variability associated with conventional basal insulins. This trial compared the glycemic control, risk of hypoglycemia, and effect on body weight of insulin detemir and NPH insulin in patients with type 1 diabetes treated with rapid-acting insulin aspart at meals. RESEARCH DESIGN AND METHODS-This study was a 6-month multinational open parallel-group comparison conducted at 46 center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
204
2
12

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 276 publications
(251 citation statements)
references
References 28 publications
28
204
2
12
Order By: Relevance
“…In this trial, a significantly lower mean body weight was observed in the insulin detemir/insulin aspart group than in the NPH/regular human insulin group after 18 weeks of treatment. This finding is consistent with findings from other trials with insulin detemir [14,16]. The reason for the difference in weight development is likely to be a difference in food intake, probably due to less defensive snacking in the insulin detemir/insulin aspart group, related to the lower variability in plasma glucose and the reduced risk of hypoglycaemic episodes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this trial, a significantly lower mean body weight was observed in the insulin detemir/insulin aspart group than in the NPH/regular human insulin group after 18 weeks of treatment. This finding is consistent with findings from other trials with insulin detemir [14,16]. The reason for the difference in weight development is likely to be a difference in food intake, probably due to less defensive snacking in the insulin detemir/insulin aspart group, related to the lower variability in plasma glucose and the reduced risk of hypoglycaemic episodes.…”
Section: Discussionsupporting
confidence: 91%
“…In the current trial and earlier studies, insulin detemir has been shown to have a smooth time-action profile, meeting patients' basal insulin requirements [13,14]. This profile as well as the improved overall and postprandial glycaemic control obtained in this trial indicates that the combination of insulin detemir and insulin aspart provides near-normal insulin profiles, demonstrating the advantages of these new insulin analogues.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations